Pengaruh Teknik Massage Endorphin Dan Teknik Relaksasi Nafas Dalam Terhadap Nyeri Persalinan - Katili, Dwi Nur Octaviani; Djunaid, Ulfiana; Melani, Noer Arriza Dwi; Yunus, Yuliandary; Harisa, Karmila (Poltekkes Kemenkes Kendari, 2023)
Labor pain can cause stress which causes excessive release of ketacolamine and steroids. This hormone can cause smooth muscle tension and vasoconstriction of blood vessels. The purpose of this study was to determine the effect of endorphin massage techniques and deep breathing relaxation techniques for labor pain in the first phase of active phase in the delivery room at Sitti Khadijah Hospital. The research design used was quasi experimental nonequivalent control group design. The sampling technique uses purposive sampling with a total sample of 26 respondents. Bivariate analysis used was paired sample t-test and independent sample t-test. The results showed there was a decrease in labor pain after endorphin massage techniques and deep breathing relaxation techniques with a p-value of 0,000 ? <0.05. In conclusion, endorphin massage techniques and breathing relaxation techniques significantly influence labor pain during the active phase.